URGENCY AND STRATEGY OF WASTE MANAGEMENT ON NATURAL TOURISM AREAS IN INDONESIA: LITERATURE REVIEW - Putri Ratna Setyowati; Trisno Fallo; Gangsar Edi Laksono (Universitas Negeri Medan, 2024)
Nowadays, natural tourism waste management in Indonesia has begun to be considered asone of the priorities of all circles. Tourist visits to this natural tourist area will have apositive and negative impact. One of the positive impacts that arise is the economicturnaround and the improvement of welfare. However, along with the increase in humanactivities, there is a negative impact on the environment, namely the increase in wastegeneration. Existing tourism must remain based on environmental sustainability so that theimage of a natural tourism area continues to be maintained. As the number of touristdestinations and visitors increases, waste management in natural tourism areas is also anurgency that must be considered. The aim of this study is to examine the urgency andmanagement strategies of natural tourism areas in Indonesia. The research method used isdescriptive exploratory based on literature review. Through a systemic waste managementstrategy, the waste problem will be handled. Waste management strategies that can becarried out are simple management, reduction and restriction activities by natural tourismarea managers, 3R-based management such as waste banks and TPS3R, support frompolicy stakeholders in the form of providing binding facilities and regulations, and thedevelopment of ecotourism-based natural tourism areas.